Implications of Individual Behavioral Patterns to the Monitoring and Evaluation Process of Fee Free Basic Education Policy in Tanzania: A case of Mwanza Region, Tanzania - David Balyagati; Emmanuel Nyankweli (Eximia, 2024)
It is an unidentified prerequisite a resoluteness that individuals’ behavioral patterns have insinuations to the monitoring and evaluation process. Academic literature reviewed by this fixes an intermittent of texts on how behavioral patterns lesser to the M&E process of fee-free basic education policy in Tanzania. This study used knowledge, persuasions, appreciation, and beliefs as part of individuals’ behavioral patterns on how they influence the relevance, efficiency, effectiveness, impacts, and sustainability of fee-free basic education provision policy. The study was conducted in the Mwanza region in Tanzania by local government authorities of Mwanza City Council, Ilemela municipality, and district councils of Ukerewe, Sengerema, Magu, Kwimba, and Buchosa. A sample size of 195 respondents was selected purposively from stakeholders of fee-free basic education provision policy. Data collected through questionnaires were analyzed using MATLAB-based Minitab software tested as one sample t-test. Statistical and practical significance were used to interpret the results. The findings illustrate that p(β<α=0.05) and µm < µ, designates that knowledge, persuasions, appreciation, and beliefs emerge, as well as upshot and engraving to the performance indicators on the M&E of fee-free basic education provision policy. The results propose projected behavioral patterns elements that emerge to be added to enhance the M&E process as a discipline of study; in future research, it may be interesting to compare and contrast the findings in addition to this longitudinal data might be more trustworthy to validate the findings.